Decision Support System for used Car Selection Recommendations using the TOPSIS Method - Bustanul Arifin (International Journal of Basic and Applied Science, 2021)
Information about used cars for sale can help consumers in buying vehicles. But sometimes people often forget, especially if the criteria are very numerous such as the price of cars, interior accessories, exterior accessories, passenger capacity and year of production so that consumers often experience mistakes in choosing used vehicles to buy. Therefore we need a system that can provide recommendations using the right method, the following is a decision support system method including Fuzzy Multiple Attribute Decision Making. One of the mechanisms to solve FMADM problems is by applying the TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) method.